2008
DOI: 10.1007/s10719-008-9150-8
|View full text |Cite
|
Sign up to set email alerts
|

Neo-glycopeptides: the importance of sugar core conformation in oxime-linked glycoprobes for interaction studies

Abstract: Carbohydrate binding proteins, such as lectins, are crucial in numerous biological recognition processes. While binding may be mediated by a single monosaccharide, several lectins have shown exquisite epimer and linkage recognition indicating that a larger structure is essential for optimal interaction. Several approaches have been described for their detailed study, including lectinosorbent assays, microarrays and surface plasmon resonance (SPR). Most of these approaches ignore that the aglycon-bound monosacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…We believe that the observed limited interaction of AMB conjugates with lectins, as opposed to M-AMB and B-AMB conjugates, are due to the fact that the glycans are presented by the former linker with anomeric heterogeneity (oxime tautomer), where the open-chain isomer is the one most represented (approximately 75 % for both lactose and N-acetyllactosamine [39] and close to 100 % with mannose [40] ) whereas the latter give rise only to ringclosed conjugates. [41] Such rationalization is in line with findings of Shin et al [42] who, after solution NMR spectroscopic and on-slide reactivity studies, related higher fluorescence signals upon lectin binding for glycans applied to hydrazide vs. hydroxylamine coated glass slides to the nature of the anomeric linkage established on the surface.…”
Section: On-chip Glycan-linker Conjugates Assay With Lectinsmentioning
confidence: 95%
“…We believe that the observed limited interaction of AMB conjugates with lectins, as opposed to M-AMB and B-AMB conjugates, are due to the fact that the glycans are presented by the former linker with anomeric heterogeneity (oxime tautomer), where the open-chain isomer is the one most represented (approximately 75 % for both lactose and N-acetyllactosamine [39] and close to 100 % with mannose [40] ) whereas the latter give rise only to ringclosed conjugates. [41] Such rationalization is in line with findings of Shin et al [42] who, after solution NMR spectroscopic and on-slide reactivity studies, related higher fluorescence signals upon lectin binding for glycans applied to hydrazide vs. hydroxylamine coated glass slides to the nature of the anomeric linkage established on the surface.…”
Section: On-chip Glycan-linker Conjugates Assay With Lectinsmentioning
confidence: 95%
“…Surface plasmon resonance is one of the most important techniques used in this area and a number of groups have developed different approaches for the immobilization of carbohydrates on sensor chips. [52][53][54][55] In many cases SAMs are formed by the covalent binding of thiols to gold. [56][57][58][59] For example, Zhi et al reported a concept that could be applied to synthetic glycosides and glycans from natural sources.…”
Section: Synthesis Of Disaccharide Allyl Glycosidesmentioning
confidence: 99%
“…A comparative study on the functionality of both types of neoglycopeptides (with versus without N9-methylation) in carbohydrate-lectin interaction studies by SPR was done; both nuclear magnetic resonance and mass spectrometry data demonstrated that for the non-methylated aminooxy function a rather unfavorable 70:30 distribution of open versus closed structures existed. SPR interaction studies with several lectins showed higher responses of the N9-methylated glycopeptides, indicative of a single binding event and in contrast with the behavior of non-methylated analogs (109). Hydrazide is another nucleophile employed to conjugate carbohydrates to peptides, with a strong a-effect that preserves a cyclic conformation of the sugar.…”
Section: Non-natural Glycosidic Linkagesmentioning
confidence: 99%